Expression of human leukocyte antigen-e and natural killer cells in intra uterine fetal death - Sulistyowati, Sri; Nugroho, Muhammad Anggit; Respati, Supriyadi Hari; Soetrisno, Soetrisno (Folia Medica Indonesiana, 2017)
Intra Uterine Fetal Death (IUFD) is one contributor to infant mortality. Human Leukocyte Antigen-E (HLA-E) and Natural Killer Cells (NK cells) are believed to play an important role towards IUFD associated with immune maladaptation. This study aimed to determine the expression of HLA-E and NK cells on trophoblast on IUFD and normal pregnancy. The study used cross sectional approach undertaken at Department of Obstetrics and Gynecology, Dr. Moewardi Hospital, Surakarta, networking hospitals, and Anatomic Pathology Laboratory of Faculty of Medicine, Sebelas Maret University. The number of samples were 32 subjects consisting of 16 subjects with normal pregnancy and 16 subjects with IUFD. The expression of HLA-E and NK cells on trophoblast of subjects who met the inclusion and exclusion criteria were examined using immunohistochemistry method and t-test statistical analysis. The mean value of HLA-E expression in the trophoblast of IUFD group was 17.30±6.69, in normal pregnancy was 57.06±32.04, with p=0.00 (p<0.05). The mean value of NK cell expression in trophoblast in IUFD group was 78.62±36.43, in normal pregnancy was 19.87±6.43, with p=0.00 (p<0.05). This study concluded that the expression of HLA-E was lower and NK cells wass higher in IUFD compared to those in normal pregnancy.